2023
DOI: 10.3389/or.2023.10576
|View full text |Cite
|
Sign up to set email alerts
|

Changing Colorectal Cancer Trends in Asians: Epidemiology and Risk Factors

Abstract: Once an infrequent disease in parts of Asia, the rate of colorectal cancer in recent decades appears to be steadily increasing. Colorectal cancer represents one of the most important causes of cancer mortality worldwide, including in many regions in Asia. Rapid changes in socioeconomic and lifestyle habits have been attributed to the notable increase in the incidence of colorectal cancers in many Asian countries. Through published data from the International Agency for Cancer Research (IARC), we utilized avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 89 publications
(102 reference statements)
4
8
0
Order By: Relevance
“…Similarly, results showed that gender played a role in the difference in GI cancer incidence, particularly gastric and liver cancers, males having 2.8, 2.4 and 1.7 times more likely to get the cancers respectively. This nding is in line with current literature (Cruz et al 2019;Pardamean et al 2023;Scherübl 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, results showed that gender played a role in the difference in GI cancer incidence, particularly gastric and liver cancers, males having 2.8, 2.4 and 1.7 times more likely to get the cancers respectively. This nding is in line with current literature (Cruz et al 2019;Pardamean et al 2023;Scherübl 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The in uence of ethnicity is also evident in subsets colorectal, pancreatic and oesophageal cancers in this study. Epidemiological studies have examined the association between ethnicity, speci cally White and Asian populations, and gastrointestinal malignancies, including colorectal, pancreatic, esophageal, gastric, and liver cancer (Arnold et al 2020;Ashktorab et al 2017;Liu et al 2020;Pardamean et al 2023;Wang et al 2022). Similarly, results showed that gender played a role in the difference in GI cancer incidence, particularly gastric and liver cancers, males having 2.8, 2.4 and 1.7 times more likely to get the cancers respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1993 and 2010, age-standardized CRC incidence rates consistently rose in various Asian countries, with South Korea experiencing the most signi cant increase. 3 According to agestandardized incidence rates, CRC ranks among the top three cancer types in many Asian countries. 21 The differing incidence rates of CRC among various racial groups can be attributed to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…These changes encompass factors such as obesity, tobacco usage, and the consumption of spicy food, alcohol, and meat. 3 The dietary pattern in South America, characterized by high consumption of beef and fats and low intake of bers, could be associated with an elevated risk of CRC. 23 However, the rise in CRC incidence in South America has not matched the signi cant increase observed in East Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation